Donor-derived cell-free DNA predicted allograft rejection and severe microvascular inflammation in kidney transplant recipients - Kim, Hyung Duk; Bae, Hyunjoo; Kang, Hyunhye; Lee, Hanbi; Eum, Sang Hun; Yang, Chul Woo; Choi, Yeong Jin; Chung, Byung Ha; Oh, Eun-Jee (Frontiers in Immunology, 2024)
Introduction: The aim of this study is to investigate the clinical validity of donor-derived cellfree DNA (dd-cfDNA) in comparison with that of donor specific anti-HLA antibody (DSA) for predicting biopsy-proven rejection (BPR)and severe microvascular inflammation (severe MVI) in kidney transplant recipients (KTRs). Methods: In this prospective observational investigation, 64 KTRs who underwent the indicated biopsies were included. Blood samples collected prior to biopsy were tested for dd-cfDNA and DSA. Biopsy specimens were classified by a renal pathologist according to the Banff classification. The predictive performance of dd-cfDNA and DSA for histological allograft diagnosis was assessed.Results: KTRs were categorized into the high and low dd-cfDNA groups based on a level of 0.4%. Eighteen patients (28.1%) had positive DSA at biopsy, exhibiting higher dd-cfDNA levels than the DSA-negative patients. BPR and severe MVI incidences were elevated in the high dd-cfDNA group (BPR: 42.9% vs. 3.4%, P <0.001; severe MVI: 37.1% vs. 3.4%, P = 0.001). Also, elevated glomerulitis and MVI scores were observed in the high dd-cfDNA group. DSA showed the highest predictive value for BPR (AUC = 0.880), whereas dd-cfDNA alone excelled in predicting severe MVI (AUC = 0.855). Combination of DSA and dd-cfDNA (>0.4%) yielded sensitivities of 80.0% and 50.0% with specificities of 90.7% and 88.0% for antibody-mediated rejection and severe MVI detection, respectively.The dd-cfDNA test is a predictive tool for BPR and severe MVI, and it can improve the performance, especially when combined with DSA for BPR.